1995
DOI: 10.1093/oxfordjournals.humrep.a136060
|View full text |Cite
|
Sign up to set email alerts
|

Implantation: Leukaemia inhibitory factor in human endometrium during the menstrual cycle: cellular origin and action on production of glandular epithelial cell prostaglandin in vitro

Abstract: Leukaemia inhibitory factor (LIF) is a pleiotrophic cytokine which plays an obligatory role in mouse implantation. To investigate its potential role in the regulation of uterine function in the human, LIF secretion by isolated human endometrial glandular epithelial and stromal cells in primary culture was determined. Endometrial cells secreted a detectable amount of LIF protein during the first 48 h of culture. In the follicular and late-luteal phases, LIF secretion by both cell types was low. At every stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 0 publications
1
21
1
3
Order By: Relevance
“…The results of the present study support an earlier observation that LIF production in human endometrium in vitro was not affected by a low dose of RU486 (Chaouat et al 1995). Similar to earlier reports in the human (Charnock-Jones et al 1994, Arici et al 1995, Chen et al 1995, Vogiagis et al 1996, we also observed only low to moderate levels of LIF in the stromal compartment of mid-luteal phase endometrium in the rhesus monkey. There was, however, a marginal increase in the level of LIF in the vascular compartment.…”
Section: Effect Of Luteal Phase Ru486 On Endometrial Lif Tgf Vegf supporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study support an earlier observation that LIF production in human endometrium in vitro was not affected by a low dose of RU486 (Chaouat et al 1995). Similar to earlier reports in the human (Charnock-Jones et al 1994, Arici et al 1995, Chen et al 1995, Vogiagis et al 1996, we also observed only low to moderate levels of LIF in the stromal compartment of mid-luteal phase endometrium in the rhesus monkey. There was, however, a marginal increase in the level of LIF in the vascular compartment.…”
Section: Effect Of Luteal Phase Ru486 On Endometrial Lif Tgf Vegf supporting
confidence: 92%
“…Available studies in the human also indicate that endometrial LIF synthesis and secretion are high during the mid-luteal phase, that is, around the time of blastocyst implantation (Charnock-Jones et al 1994, Kojima et al 1994, Arici et al 1995, Chen et al 1995, Cullinan et al 1996, Vogiagis et al 1996. Several cytokines which are influenced by progesterone have been found to enhance endometrial LIF expression (Arici et al 1995).…”
Section: Effect Of Luteal Phase Ru486 On Endometrial Lif Tgf Vegf mentioning
confidence: 99%
“…The process of decidualization is characterized by dramatic morphological and biochemical transformation of ESCs into secretory decidual cells that is associated with the production of cytokines, growth factors, and inflammatory mediators essential for blastocyst development and implantation [28,30,31]. For instance, ESCs have been demonstrated to release a number of factors like leukemia inhibitory factor (LIF) [32], granulocytemacrophage colony-stimulating factor (GM-CSF) [33], insulinlike growth factor (IGF) [34], epidermal growth factor (EGF) [35], and IL-6 [36,37] that have been found to exert a direct beneficial effect on embryonic development, growth rates, and implantation potential [3,4,26,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…LIF está expresso em vários tecidos embrionários e adultos Em humanos, LIF mRNA e proteína são expressos em glândulas endometriais durante a fase lútea do ciclo menstrual, período em que ocorre a implantação (CHEN et al, 1995). LIF-Rβ e gp-130 são expressos no epitélio luminal ao longo do ciclo de mulheres comprovadamente férteis (GULLINAN et al, 1996).…”
Section: Fator Inibidor De Leucemia (Leukemia Inhibitory Factor -Lif)unclassified